(untitled) (Bangladesh Journal of Child Health, 2018)
Introduction: Anemia of prematurity (AOP) is a common problem of very low birth weight babies. Blood transfusion is a necessity when it occurs in moderate to severe form putting the child in to the risk of transfusion related complications. Erythropoietin, a potent stimulator of hemopoesis is available in breast milk in good amount and absorbed intact under physiologic condition. In this background oral recombinant human erythropoietin (rhEPO) can be a useful alternative to its subcutaneous administration in prevention of AOP. Objective: To evaluate the efficacy of oral rhEPO in the prevention of AOP in very low birth weight (VLBW) neonates. Methods: This randomized controlled study conducted in the NICU of BSMMU over one year. Total 60 preterm (<34 weeks)VLBW (<1500g) infants were enrolled and randomly divided into Control (group-I), Oral (group-II) and Subcutaneous (group III). Experimental groups (group-II & group-III) received rhEPO 400 IU/Kg, 3 times weekly in oral and subcutaneous (S/C) route respectively and continued for 2 weeks (Total 6 doses). Therapy was initiated 14 days after birth when the baby achieved oral feeding of at least 50 ml/kg/day of breast milk. All infants received oral iron and folic acid supplementation up to 12 weeks of postnatal age. Transfusion data were recorded. Anthropometric and hematological assessments were done at 2, 4, 6 and 12 weeks of age. Results: Baseline clinical characteristics and hematological values were almost similar in all groups. Mean hemoglobin were 11.34±0.68gm/dl, 11.88±0.54gm/dl& 12.12±1.32 gm/dl, the mean hematocrit were 34.11±2.03%, 35.66±1.65% & 36.38±3.97% and the mean reticulocyte were 7.56±2.48%, 9.85±1.50% & 9.22±3.11% in the control, oral and subcutaneous group respectively and the differences are statistically significant (p<0.05).Weight gain was higher in the intervention group at 6 and 12 weeks follow up than the control group(p<0.05).Only 2 (5.25%) infants, one in each of the intervention groups required blood transfusion, compared to 6 (31.5%) infants in control group (p<0.01). Conclusion: Oral EPO is as good as subcutaneous use of EPO in stimulating erythropoesis, maintaining HCT and Hb at high level and is safe in preterm baby. Bangladesh J Child Health 2017; VOL 41 (2) :101-109